i1 : A = typeA 6;
|
i2 : F = flat(A, {0, 1, 6, 15, 20})
o2 = {0, 1, 6, 15, 20}
o2 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i3 : G = flat(A, {0, 1, 2, 6, 7, 11})
o3 = {0, 1, 2, 6, 7, 11}
o3 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i4 : H = flat(A, {0, 1, 2, 3, 6, 7, 8, 11, 12, 15})
o4 = {0, 1, 2, 3, 6, 7, 8, 11, 12, 15}
o4 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i5 : F ^ G
o5 = {0, 1, 6}
o5 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i6 : G ^ H
o6 = {0, 1, 2, 6, 7, 11}
o6 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i7 : F ^ H
o7 = {0, 1, 6, 15}
o7 : Flat of {x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x , x - x }
1 2 1 3 1 4 1 5 1 6 1 7 2 3 2 4 2 5 2 6 2 7 3 4 3 5 3 6 3 7 4 5 4 6 4 7 5 6 5 7 6 7
|
i8 : assert(meet(F, G) === F ^ G)
|
i9 : assert(F ^ G === G ^ F)
|
i10 : assert((F ^ G) ^ H === F ^ (G ^ H))
|
i11 : assert(G ^ G === G)
|